Рождение ребёнка с обвитием пуповиной: взгляд с позиций гелиобиологии - Назаренко, Л.Г.; Семеринская, И.А.; Беляев, С.Г. (Таврический медико-биологический вестник, 2012)
Вивчено взаємозв'язок циклічних змін сонячної активності та геомагнітного поля Землі з частотою
народження дітей з обвиттям пуповиною. Встановлено, що сезон народження дитини не має зв'язку з
імовірністю обвиття пуповиною. Studied interrelation of the cyclic variations of solar activity and geomagnetic field of the Earth
with a frequency of birth of children with umbilical cord twist. It is established, that time of the year of
birth of the child has no relation with the probability of the umbilical cord twist.